Effect Zinc Ion Concentration on Structural and Optical Properties of ZnS Thin Films Prepared by Chemical Bath Deposition Technique - Hani H. Ahmed; Faris S. Atallah (College of Education for Pure Sciences, 2013)
Abstract In this work, ZnS films were prepared by chemical bath deposition technique where the zinc nitrate salt (Zn(NO3)2) was used as a source of zinc ions(Zn+2) and thiourea (SC(NH2)2) as a source of negative sulphide ions(S-2). The effect cadmium ion concentration at 0.05 M and 0.1 M on the structural and optical properties is described. Annealing process is carried out in air at temperature 473K for 2h. The structural properties were studied by X-ray diffraction, where found that for ZnS films